Kualitas Fisik Kombinasi Beberapa Legum di dalam Wafer Jerami Padi: Physical Quality of Combination of several Legumes in Rice Straw Wafers - Fridarti, Fridarti; Andika , Redi; Zulkarnaini, Zulkarnaini; Dianti, Devi; Jefri, PN (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2025)
Background: During the harvest season, rice straw can be one of the agricultural wastes available in large quantities. If preserved by drying in the sun, then stored in a place procted from rain, the material can be used as a reserve of animal feed during the dry season. To improve the nutritional quality of west example the straw, it is necessary to process it by fermentation, apart from that you can also add legumes to animal feed. To increase efficiency in feeding livestock, it is best to make the feed in wafer form. Wafers are a technology that is quite effective in maintaining the continuity of animal feed, especially during the dry season. Purpose: The objective of this study was to ascertain the optimal concentration of Tiwai onion nano particles and how their feeding to broiler chickens affects broiler performance. Methods: Using a completely randomised complete block design (CRD), this study included five replicates and five treatments, each consisting of 4 broilers and reared until 35 days of age. Feed consumption, body weight gain, feed conversion, final body weight, and mortality were the parameters of the study. Onion tiwai nanoparticles were administered at P0 which is the control or without the administration of nano particles. P1 0.2%, P2 0.4%, P3 0.6% and P4 (0.8%) contained tiwai onion. The data obtained were analysed using One Way Anova followed by Duncan's Test to examine the values of feed consumption, body weight gain, feed conversion, final body weight, and mortality. Results: The study showed that the administration of tiwai onion nanoparticles had no significant effect (P>0.05) on feed consumption, body weight gain, feed conversion, final body weight and mortality. Conclusion: Giving tiwai onion nanoparticles as a feed additive at a dose of 0.2% - 0.8% / kg had no significant effect on feed consumption, FCR, PBB, final body weight and mortality. Giving nano particles of tiwai onions is able to maintain health in livestock because the content of tiwai onions as a feed additive is able to increase the immune system antiviral, and as well as anti-bacterial which can reduce bacterial growth so that the mortality rate in the study was 0% or no deaths.